3D ultrasound findings in women attending a South Australian recurrent miscarriage clinic. Issue 4 (28th October 2016) - McCormack, Catherine D.; Furness, Denise L.; Dekker, Gustaaf A.; Shand, Karen; Roberts, Claire T.
Abstract: Background: Women who suffer recurrent miscarriage are a heterogeneous group. Known causes include genetic and endocrine abnormalities, anti‐phospholipid syndrome and autoimmune disease. Congenital uterine abnormalities (CUAs) such as bicornuate, unicornuate, septate and arcuate uterine abnormalities are known to negatively impact on pregnancy rates, and to increase the miscarriage rates of genetically normal pregnancies. In some countries, such as Britain, 3D ultrasound of the pelvis is offered routinely to women with recurrent miscarriages. Aim: To determine the prevalence of CUAs and other pelvic pathology, in women attending a South Australian recurrent miscarriage clinic. Materials and methods: 3D transvaginal ultrasounds performed during the luteal phase of the menstrual cycle were offered to all patients attending the recurrent miscarriage clinic, who had not previously had a hysteroscopy, laparoscopy, HyCoSy or MRI study of their pelvis. A Philips IUI 8 MHz transvaginal probe for freehand sweep, and dedicated 3D transvaginal probe was used. 3D scans provide a coronal view of the uterus, ideal for detecting abnormalities which may be missed during routine conventional 2D scanning. Results: A total of 210 women were recruited, 200 results were available, and 29% were found to have a CUA. 15% had polycystic ovaries detected, 15% were found to have fibroids, 12% adenomyosis and 1.5% Asherman's syndrome. Conclusions: 3D ultrasound evaluation of patients attending a recurrent miscarriage clinic detects CUAs, and has a high detection rate of other pelvic abnormalities that may contribute to recurrent miscarriages.